1974
DOI: 10.1111/j.1432-1033.1974.tb03671.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteinase K from Tritirachium album Limber

Abstract: The fungus Tritirachium album Limber was grown by submerged fermentation, investigating the conditions for maximal secretion of proteases into the medium. Enzyme secretion starts when the stationary phase of growth is reached, and when the culture medium is depleted of glucose and amino acids, suggesting a catabolite repression of the enzyme.The main proteolytic enzyme was named proteinase with respect to its keratin hydrolyzing activity. It was isolated from the culture medium and purified by crystallization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
345
0
6

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 578 publications
(359 citation statements)
references
References 20 publications
8
345
0
6
Order By: Relevance
“…The predominant site of cleavage is the peptide bond adjacent to the carboxyl group of aliphatic and aromatic amino acids with blocked alpha amino groups. Raising the temperature of proteinase K from 37 o C to 50-60 o C can increase its activity several fold [23]. We found that proteinase K was more efficient than QIAgen protease, and that incubation at 37 o C gave better results than RT or 50 o C on CFDNA purification.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The predominant site of cleavage is the peptide bond adjacent to the carboxyl group of aliphatic and aromatic amino acids with blocked alpha amino groups. Raising the temperature of proteinase K from 37 o C to 50-60 o C can increase its activity several fold [23]. We found that proteinase K was more efficient than QIAgen protease, and that incubation at 37 o C gave better results than RT or 50 o C on CFDNA purification.…”
Section: Discussionmentioning
confidence: 78%
“…Figure 1 shows that pre-incubation of serum samples with proteinase K (400 µg/ml) at 37 o C for 1 hour (Q 37-1, P 37-1 ) significantly increased the DNA recovery compared to no incubation (Q N, P N ) (Q N vs Q 37-1 : p = 0.003; P N vs P 37-1 : p = 0.002) and there was significantly better DNA yield with proteinase K than the QIAgen protease (Q N vs P N: p = 0.040). However, longer incubation time (2 hours) and incubation at 50 o C [23] did not improve the DNA yield further (data not shown).…”
Section: Optimization Of Qiaamp Protocolmentioning
confidence: 88%
“…Proteinase K (PRK1) is reported to have great potential for basic and applied research due to its broad peptide cleavage activity, unusual stability over a wide range of temperatures and pH values and even in the presence of low concentrations of SDS and urea (Ebeling et al 1974). Based on the present observation on the physiochemical, structural and sequence similarities of EAP with proteinase K, along with our previous report on the high pH and temperature optima of EAP (Chellappan et al 2006), it is proposed that marine fungal isolate of E. album has the potential to serve as an alternative cum additional source of alkaline protease enzyme for various industrial and research applications.…”
Section: Discussionmentioning
confidence: 99%
“…Proteinase K is a serine protease that exhibits very broad cleavage specificity, cleaving peptide bonds adjacent to the carboxylic group of aliphatic and aromatic amino acids (Ebeling et al, 1974). Since completely folded proteins are less accessible to cleavage by proteinase K compared to unfolded and/or denatured proteins, the proteinase K assay can be used to obtain qualitative information about the structural integrity of proteins.…”
Section: V22 Structural Characterization Of Fluc Variants In Rrl Vmentioning
confidence: 99%